Tata Laksana Oral Mukositis pada Keganasan Anak - Siska Natalia Situmeang; Bidasari Lubis; Nelly Rosdiana; Selvi Nafianti; Olga Rasiyanti Siregar (PT Dexa Medica, 2021)
Malignant disease or cancer is a disease caused abnormal growth of certain cells, characterized continuous, unlimited growth, uncoordinated with surrounding tissue and not functioning physiologically. According to the National Cancer Institute, there was a significant increase in the number of pediatric cancers in United States from 13.8 per 100,000 children in 1973 to 17.6 per 100,000 children in 2005. Chemotherapy shows high efficacy in the treatment of cancer in children, especially on cancer that can not be treated by surgery or radiation alone. Radiation therapy can be used as a curative therapy to reduce tumor size or as palliative to alleviate symptoms. However, the administration of chemotherapy and radiotherapy associated with many side effects. Mucositis is a reactive process that resembles inflammation on the oropharynx mucous membranes, and often accour as the side effect of chemotherapy or radiotherapy. Management of oral mucositis in children who receive chemoradiation varies, both pharmacologically and nonpharmacologically. At present, there is no gold standard for management of oral mucositis in children.